The Relationship between ABO Blood Type and Outcomes in Severe and Critical COVID-19 Patients in the Covid ICU of the Hospital. Dr. M. Djamil Padang - Benanda, Adissa; Kurnia, Dedy; Akhyar, Gardenia (Jurnal Indonesia Sosial Sains, 2024)
The spread of the Coronavirus Disease represents the most significant global health threat in recent decades. Blood type is among the risk factors associated with COVID-19, with certain blood types linked to increased severity and higher mortality rates. This research aims to assess the relationship between ABO blood type and outcomes in severe and critical COVID-19 patients in the ICU at RSUP Dr. M. Djamil Padang. The study is an observational analytical research utilizing a cross-sectional approach. Data were gathered from the medical records of COVID-19 patients from January to September through a total sampling method, resulting in 124 individuals meeting the inclusion criteria. The data were analyzed utilizing the Chi-Square test. The discoveries uncovered that male patients (54%) dwarfed female patients (46%). The larger part of patients were within the age range of 56-65 for years (33.9%). Patients with blood sort O were more predominant among those with extreme COVID-19 (31.3%) and basic COVID-19 (38.0%). The foremost common result was passing, happening in 56.0% of serious cases and 53.7% of basic cases. There was no factually noteworthy relationship between ABO blood sort and results in serious and basic COVID-19 patients, with a p-value of 0.778 (>0.05). The study concludes that there's no measurably critical affiliation between ABO blood sort and outcomes in extreme and basic COVID-19 patients within the ICU at Dr. M. Djamil Padang hospital.